The Role of Group Dynamics in Resolving Conflict - Zen, Dendy Saeful; Iskandar, Deden; Nirwana, Hanita; Suharyati, Henny (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
The main objectives of this study were to understand how group dynamics can influence a group's ability to resolve conflicts and to identify the internal and external factors that influence a group's ability to resolve conflicts. The method used in this research is a literature study. Literature review is a study that examines or critically evaluates knowledge, ideas and findings in academically oriented literature and formulates theoretical and methodological contributions on a particular topic. The results of research using literature review include the definition of conflict, the origin of conflict, types of conflict and conflict resolution techniques. Conflict can arise because one party or one party feels disadvantaged. This loss can be material or non-material. Group dynamics an effort to accelerate the dynamics of all participants and led training groups so that the group becomes more dynamic and the goals and objectives of training become more effective, efficient and quality. Conclusion In conflict resolution, it is important to find solutions that integrate different interests and encourage cooperation. Constructive cooperation and the ability to compromise can help achieve a more satisfactory outcome for all parties. Keep in mind that each collective conflict has its own dynamics and no one approach can be generalized.